Mesenchymal stem cells from cortical bone demonstrate increased clonal incidence, potency, and developmental capacity compared to their bone marrow–derived counterparts - Blashki, Daniel (J Tissue Eng, 2016)
In this study, we show that matrix dense cortical bone is the more potent compartment of bone than bone marrow as a stromal source for mesenchymal stem cells as isolated from adult rats. Lineage-depleted cortical bone-mesenchymal stem cells demonstrated >150-fold enrichment of colony forming unit–fibroblasts per cell incidence. compared to lineage-depleted bone marrow-mesenchymal stem cells, corresponding to a 70-fold increase in absolute recovered colony forming unit–fibroblasts. The composite phenotype Lin(−)/CD45(−)/CD31(−)/VLA-1(+)/Thy-1(+) enriched for clonogenic mesenchymal stem cells solely from cortical bone–derived cells from which 70% of clones spontaneously differentiated into all lineages of bone, cartilage, and adipose. Both populations generated vascularized bone tissue within subcutaneous implanted collagen scaffolds; however, cortical bone–derived cells formed significantly more osteoid than bone marrow counterparts, quantified by histology. The data demonstrate that our isolation protocol identifies and validates mesenchymal stem cells with superior clonal, proliferative, and developmental potential from cortical bone compared to the bone marrow niche although marrow persists as the typical source for mesenchymal stem cells both in the literature and current pre-clinical therapies.